Reinventing Nuremberg. The Fight Against Impunity in Latin America and the Transformation of Criminal Law - Stahl, Daniel (Journal of Genocide Research, 2025)
Legal innovations in International Criminal Law at the end of the twentieth century were often legitimized by references to the International Military Tribunal (IMT), and sometimes also to the subsequent Nuremberg Trials (NMT). This article analyses the Latin American Human Rights movement's campaigns of the 1980s and 1990s against impunity and their usage of the legal innovations of post-World War II with a special focus on Argentinean groups and their campaigns before international organizations and Argentinean and European courts. It argues that that these groups transformed the meaning of the IMT in their effort to turn criminal law into a tool to combat human rights violations, thereby inventing what this article conceptualizes as a specific Latin American Nuremberg cipher. This cipher spread across the Atlantic and gained relevance in Europe.
CRIS-Team Scopus Importer:2025-12-12
Keywords: crimes against humanity; disappearances; human rights; impunity; International Criminal Law